Seven Fundamental Movements for Conditioning Gymnasts - Sands, W. A.; McNeal, J. R.; Jemni, M. (coachesinfo.com)
Shoulder flexion - casting, press handstands, planche Shoulder extension - kipping, uprise, downswing phases of in-bar work Upper extremity pushing - handstand, handstand push up, rebounding during hand contact phases Upper extremity pulling - pull up, pullover, withstand the bottom of swinging skills Jumping and landing - tumbling, vaulting, mounts, dismounts, dance movements Torso and hip flexion - piking, tucking, leg lifts, forward somersault take offs, hollow body positions Torso and hip extension - arching, back bends, walkovers, flic flacs, most backward take offs